2022
DOI: 10.38194/jurkom.v5i2.428
|View full text |Cite
|
Sign up to set email alerts
|

Pesan Kampanye Non-Goverment Organization terhadap Permasalahan Sampah Plastik

Abstract: Pencemaran lingkungan dari  sampah plastik memiliki banyak dampak negatif yang dapat membahayakan ekosistem bumi di masa sekarang dan depan. Inisiasi perubahan dalam penggunaan plastik banyak dilakukan oleh Organisasi Non-Pemerintahan (NGO). Harapannya dengan kampanye tersebut dapat merubah aspek pengetahuan (knowledge), sikap (attitude), dan perilaku (behavioural). Penelitian ini bertujuan untuk mengetahui bagaimana pesan kampanye Non-Government organization terhadap permasalahan sampah plastik BBPB. Metode y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
0
0
1
Order By: Relevance
“…Meanwhile, the things that are the biggest supporters of the influence of the #AwasModus campaign are the most respondents giving an assessment on the invitation to refuse if they get a fraud mode with a percentage of 59.2% or 119 respondents strongly agreeing. And finally, if you look at previous research entitled "Non-Government Organization Campaign Messages on Plastic Waste Problems" (Dewi & Syauki, 2022) in this study, it was concluded that the campaign message carried out showed good results based on analysis using descriptive only. Whereas in this study, the positive results of the #AwasModus campaign message are explained by showing a more in-depth assessment using tests that can be seen in the measurement value, that the #AwasModus campaign message on Tiktok @bankbca has a positive influence of 33.1% on public financial literacy.…”
Section: Modelmentioning
confidence: 70%
“…Meanwhile, the things that are the biggest supporters of the influence of the #AwasModus campaign are the most respondents giving an assessment on the invitation to refuse if they get a fraud mode with a percentage of 59.2% or 119 respondents strongly agreeing. And finally, if you look at previous research entitled "Non-Government Organization Campaign Messages on Plastic Waste Problems" (Dewi & Syauki, 2022) in this study, it was concluded that the campaign message carried out showed good results based on analysis using descriptive only. Whereas in this study, the positive results of the #AwasModus campaign message are explained by showing a more in-depth assessment using tests that can be seen in the measurement value, that the #AwasModus campaign message on Tiktok @bankbca has a positive influence of 33.1% on public financial literacy.…”
Section: Modelmentioning
confidence: 70%
“…Penyampaian pesan yang dilakukan secara interaktif dan menarik dapat menciptakan makna dan menumbuhkan kepercayaan yang akan berimplikasi pada perubahan perilaku warga. 27 Proses edukasi melalui berbagai media, khususnya media visual menjadi salah satu upaya yang dapat dilakukan untuk menarik perhatian masyarakat. Pada dasarnya masyarakat saat ini lebih menyukai tontonan, media grafik, atau penyampaian materi secara sederhana.…”
Section: Edukasi Literasi Sampah Melalui Mediaunclassified
“…Dalam hal ini komunikator harus dapat membawa khalayak masuk ke dalam isi pesan yang disampaikan dalam kampanye. Supaya mencapai hal tersebut komunikator dapat mengulangi dan memberikan penekanan terhadap inti dari pesan kampanye (Dewi & Riskiyadi, 2022). Seperti yang dilakukan oleh BCA, yang di mana kampanye #TolakDenganAnggun disebarkan secara berulang-ulang di akun twitter @BankBCA.…”
Section: Pendahuluanunclassified